Pengembangan Aplikasi Web Pembelajaran Matematika Terintegrasi Fitur Evaluasi Otomatis - Zaenul Amri; Harianto; Handayani; M. Nurul Wathani (Fakultas Teknik Universitas Hamzanwadi, 2026)
The current development of information technology provides a significant opportunity for digital transformation in the education sector, particularly to address difficulties in understanding concepts in Mathematics at the elementary school level. Based on observations at SDN Loang Tuna, the material delivery process is still dominated by conventional teaching methods utilizing textbooks and whiteboards. The limitations of these teaching aids result in low levels of interactivity and independent learning interest among students. The purpose of this study is to design and develop an information system in the form of a web-based Mathematics e-learning application that comprehensively integrates interactive material modules with an automatic evaluation feature. The software development methodology used in this study adopts the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The stages of this methodology include the identification of system requirements, the design of interface and database architectures, programming with multi-user access rights management, and software functionality testing using the Black-Box Testing method. The results of the study indicate that the application was successfully built according to the specifications. Based on the Black-Box Testing, the system demonstrates a functionality success rate of 88%, which is categorized as highly feasible. The automatic evaluation feature is proven to have high accuracy in processing real-time grade calculations, which significantly reduces the administrative workload of teachers and provides instant feedback for students. Therefore, the interactive interface of this application is effective in increasing user engagement, making it an innovative and measurable technological solution to advance the quality of Mathematics learning.